The adoption of green HRM practices in Indonesian state-owned banks: A pathway to sustainable organizational performance - Yakup, Yakup; Karundeng, Deby Rita; Gani, Roydah; Yakup, Anggita Permata; Ishak, Olfin (International Journal of Management and Sustainability, 2025)
Amid rising global urgency around sustainability, a critical question emerges: can Green Human Resource Management (GHRM) serve as a genuine driver of sustainable performance in public institutions, or is it merely a rhetorical gesture? This study explores the dynamic interplay between GHRM practices and organizational sustainability in Indonesia’s state-owned banks, positioning employee engagement as the mediating lever. Drawing on data from 260 civil servants and analyzed using Structural Equation Modeling (SEM), the findings reveal that GHRM significantly enhances both employee engagement (β = 0.59, p < 0.01) and sustainability outcomes (β = 0.33, p < 0.01). Notably, engagement also plays a pivotal mediating role (β = 0.35, p < 0.01), translating green strategies into tangible performance outcomes. The model demonstrates robust fit indices (CFI = 0.98, RMSEA = 0.067), affirming the structural coherence of the hypothesized paths. This inquiry delves beyond numeric validation, unpacking practices such as green recruitment, sustainability-driven training, ecologically aligned performance appraisals, and environmental incentive systems. It highlights how employees who find resonance between personal values and institutional sustainability missions are more inclined to actively contribute. In bureaucratic systems often perceived as rigid, these findings suggest a possible inflection point: that culturally grounded, participative HR strategies may catalyze ecological transformation in meaningful ways. Ultimately, this research offers empirical and conceptual value to public sector institutions seeking to embed sustainability into the fabric of HR systems, with engagement acting as both a bridge and a barometer.